SURGICAL TREATMENT OF CHRONIC CYSTIC PANCREATITIS - O. N. Sled; N. V. Merzlikin; N. Yu. Sled; A. E. Popov; L. Ja. Mendeleeva; S. P. Kosmachenko; I. O. Tumakov (Бюллетень сибирской медицины)
Increasing the number of patients with complicated forms of chronic pancreatitis and pancreatic cysts observed in recent decades. Mostly people of working age are susceptible to disease. This makes the issue a social importance.The article presents a modern view of the choice of method of surgical treatment of chronic pancreatitis and cystic optimal terms of therapy, depending on the degree of “maturity” of pancreatic cysts. A detailed analysis of both traditional surgery and advanced minimally invasive treatment for pancreatic cysts is performed in this review of the literature.Emphasis is placed on radical methods of treatment, particularly in the duodenum-preserving operations. Pathogenic study is carried out. The problem of choosing the most radical and at the same time the organ-preserving technique, helping to improve the immediate and long-term results, the quality of life and social and labor rehabilitation, has not lost its relevance. Studies carried out in this area are currently important.